DIETARY HABITS AND ASSOCIATED FACTORS OF PREGNANT WOMEN ATTENDING ANTENATAL CLINICS AT TOWNSHIP HOSPITALS IN NAYPYIDAW TERRITORY, MYANMAR - Le Tandar Soe; Swe Mar Myint Lwin; Si Thu (Ikatan Sarjana Gizi Indonesia (ISAGI), 2023)
Pregnancy is a critical period during which good maternal nutrition is an important factor that affects the health of both the mother and the child. The study aims to assess the knowledge, attitudes, dietary habits and nutritional status of pregnant women. A cross-sectional descriptive study was conducted from October 2022 to February 2023 among 400 pregnant women attending antenatal clinics of four selected township hospitals at Naypyidaw Territory. Of 400 pregnant women, only 18% of the pregnant women were undernourished in this study. Few (6%) of the pregnant women had high nutritional knowledge, yet most of the pregnant women (78.5%) had favorable attitudes towards nutrition. More than half (64.8%) had good dietary habits in this study. Educational level, estimated average family income, number of antenatal visits, and nutritional knowledge of the pregnant women were significantly associated with the dietary habits of the respondents according to bivariate analysis. Multivariable logistic regression analysis revealed that the number of antenatal visits and nutritional knowledge of pregnant women were significantly influenced by their dietary habits. The pregnant women who attended more frequent antenatal visits had better dietary habits than those with less frequent antenatal visits [AOR =2.00; 95% CI (1.14,3.5), p-value=0.016)]. Additionally, pregnant women with a high nutritional knowledge level were more likely to have better dietary habits [(AOR=6.96; 95% CI (1.57, 30.98), p-value = 0.011]. Nutrition education programs should be emphasized on frequent antenatal visits to improve the nutritional knowledge and dietary habits of pregnant women.